2022
DOI: 10.1111/joor.13354
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors of primary snoring and obstructive sleep apnoea in patients with sleep bruxism: A questionnaire study

Abstract: Background: By being aware of the associated factors of primary snoring (PS) and obstructive sleep apnoea (OSA) in sleep bruxism (SB) patients, dentists may contribute to the screening and early recognition of SB patients with PS or OSA.Objective: To identify the associated factors of PS and OSA from questionnaire-based data in SB patients.Methods: A total of 968 self-reported SB patients (31.6% men; median age 44.5 years) were retrospectively enrolled. Self-reported sleep-related breathing status (viz., no sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
7
0
2
Order By: Relevance
“…Its prevalence is not well documented but patients without OSA seems to have more snoring events than OSA‐free patients 47 . Prevalence of PS in SB ranges from 7.3% 30 to 32.7% 48 . A plausible temporality between PS and BS is still to be demonstrated.…”
Section: Bruxism and Respiratory Disorders During Sleepmentioning
confidence: 97%
See 2 more Smart Citations
“…Its prevalence is not well documented but patients without OSA seems to have more snoring events than OSA‐free patients 47 . Prevalence of PS in SB ranges from 7.3% 30 to 32.7% 48 . A plausible temporality between PS and BS is still to be demonstrated.…”
Section: Bruxism and Respiratory Disorders During Sleepmentioning
confidence: 97%
“…Sleep breathing events, especially mild to moderate obstructive sleep apnoea (OSA), primary snoring (PS) and clinical conditions of upper airway obstruction such as asthma, sinusitis, rhinitis and oedema, due to hypertrophy of tonsils and adenoids have been described in literature. [28][29][30][31][32][33] The prevalence of OSA in the general population is about 22% in men and 17% in women. 34 This prevalence is age-dependent, increasing from 38% at 50 years old to up to 84% above 70 years.…”
Section: B Ruxis M and Re S Pir Atory Disorder S During S Leepmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides sleep arousal, many other factors, including sex, body mass index (BMI), and sleep staging have been reported to be associated with OSA, SB, or both. 5,[14][15][16] Further, in 56% of adults with OSA, respiratory events occur mainly in their supine position. 8 Therefore, we hypothesized that the RMMA index in supine position (RMMA_sup index) is significantly higher than RMMA index in non-supine positions (RMMA_nsup index) in adults with OSA.…”
Section: Introductionmentioning
confidence: 99%
“…Bruxism was originally thought to be a central nervous system problem, associated with anxiety, tension, and the release of stressful [4]. Recent studies have shown that bruxism may be caused by a synergistic effect of multiple factors, such as genetic factors [5], neuropsychological factors (long-term anxiety and tension) [6,7], physiological and pathological factors (malocclusion, snoring, sleep disorder) [8][9][10][11], and bad lifestyle habits (smoking, alcoholism, excessive caffeine intake) [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%